2009
DOI: 10.1007/s11423-009-9110-4
|View full text |Cite
|
Sign up to set email alerts
|

Examining elementary preservice teachers’ perspectives concerning curriculum themes for video case integration

Abstract: Video cases are becoming more and more prevalent throughout the United States to assist in the development and growth of preservice teachers' instruction. This research investigates the perspectives of preservice teachers and their naïve understandings of the kinds of learning and assistance video cases can provide in their methodology courses. Personal Construct Theory was used to uncover participants' perceptions of their needs in terms of curriculum content of video cases. Hierarchical cluster analysis reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
1
4
0
Order By: Relevance
“…Regarding facilitators, the respondents reported a critical need for in-service preschool teachers to serve as their OTVC learning facilitators, although there were significant differences across year levels, with Year 3 PPTs expressing a more urgent need. This finding echoes the prior study conducted by Kurz, Batarelo, and Middleton [6], reflecting the desire of PPTs to observe experienced experts in order to help them visualize key aspects of the teaching profession. The participants also expressed the need to engage with larger communities of preschool practitioners for future career preparation [7].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Regarding facilitators, the respondents reported a critical need for in-service preschool teachers to serve as their OTVC learning facilitators, although there were significant differences across year levels, with Year 3 PPTs expressing a more urgent need. This finding echoes the prior study conducted by Kurz, Batarelo, and Middleton [6], reflecting the desire of PPTs to observe experienced experts in order to help them visualize key aspects of the teaching profession. The participants also expressed the need to engage with larger communities of preschool practitioners for future career preparation [7].…”
Section: Discussionsupporting
confidence: 81%
“…For instance, Yadav [5] investigated pre-service elementary teachers' perception of their learning with teaching video cases and indicated that they preferred scaffolded learning with videos to improve their literacy instruction and observational abilities. Similarly, Kurz, Batarelo and Middleton [6] studied the need for teaching video cases from the perspectives of preservice elementary teachers. They found that pre-service teachers had an acute need for instructional guidance when using video cases, including the development of lesson plans, the inclusion of expert analysis, and the acquisition of classroom management and child interaction skills.…”
Section: Literature Review 21 Pre-service Teachers' Perceptions Of Vi...mentioning
confidence: 99%
“…Typically, these case studies are text-based, although there is increasing interest in the use of multi-media (or video-based) cases in support of pre-service teacher education in the literature (Cannings & Talley, 2002;Hewitt, Pedretti, Bencze, Vaillancourt & Yoon, 2003;Kurz, Batarelo & Middleton, 2009;Pedretti, Bencze, Hewitt, Romkey & Jivraj, 2008). However, there is still little evidence to support the use of video cases in in-service teacher professional development (Bencze, Hewitt & Pedretti, 2001;Copeland & Decker, 1996;Louden, Wallace & Groves, 2001;VandenBerg, 2001).…”
Section: Video Case Studiesmentioning
confidence: 99%
“…Active online participation is positively associated with better achievement of the learning outcomes; Marxa, Blumenfeld, Krajcik, & Soloway (1998) asserted that innovative educational technologies can provide "visions of enactments of innovations along with teachers" reflections". In this aspect, video cases are reported as a good medium to address needs (e.g., student engagement, classroom management, classroom discussion facilitation) of pre-service teachers (Kurz, Batarelo, & Middleton, 2009). This comes to our second postulation: P2: Echo360 fosters self-reflection in teaching practices;…”
Section: P1mentioning
confidence: 92%